2012
DOI: 10.1590/s1516-31802012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Provider training and experience for people living with HIV/AIDS

Abstract: BACKGROUND: The complexity of HIV/AIDS raises challenges for the effective delivery of care. It is important to ensure that the expertise and experience of care providers is of high quality. Training and experience of HIV/AIDS providers may impact not only individual patient outcomes but increasingly on health care costs as well. OBJECTIVE: The objective of this review is to assess the effects of provider training and experience on people living with HIV/AIDS on the following outcomes: immunological (ie. viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 1 publication
3
24
0
Order By: Relevance
“…Our findings are consistent with those of a previous systematic review demonstrating that physician HIV experience is specifically associated with improved HIV-specific outcomes, such as adherence to ART prescribing. 2 Another review conducted by the same authors 3 attempted to distinguish physician training from physician HIV experience, and mainly concluded that both are important for HIV-specific outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with those of a previous systematic review demonstrating that physician HIV experience is specifically associated with improved HIV-specific outcomes, such as adherence to ART prescribing. 2 Another review conducted by the same authors 3 attempted to distinguish physician training from physician HIV experience, and mainly concluded that both are important for HIV-specific outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that clinicians with more HIV training, HIV experience, or both provide higher quality of care as measured by disease-specific indicators, including ART prescribing. [1][2][3][4][5][6] Many of these studies, however, were performed early in the ART era, when both disease and treatments were novel and complex. Recent work has found similar quality of HIV-specific care between generalist and specialist physicians, even though the HIV experience of these physicians varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the predominant source of HIV care has been in HIV/infectious diseases specialty clinics. [15][16][17] Given the numerous advances to combination ARV, HIV has now evolved into a chronic disease that can be managed in the outpatient care setting. 18 Nevertheless, there is still the need for specialty training for any provider caring for PLWH, particularly primary care providers practicing in nonspecialty settings.…”
Section: Discussionmentioning
confidence: 99%
“…The barriers include a range of issues encountered in clinical interactions with patients such as lack of time, lack of availability of educational resources and training, lack of reimbursement, difficulties in maintaining privacy/confidentiality, and lack of counselling. Training has been identified as one of the major means of improving the quality of STI care [52, 53]. Physicians’ training has been reported to be associated with improved physicians’ comfort with STI patients [43, 54]; lower prejudicial attitude toward people living with HIV/AIDS [55]; improved skill for risk assessment, clinical examination, diagnosis and treatment [52]; more willingness to offer STI testing to patients [36]; improved patient adherence [56] and improved patient’s outcomes [53].…”
Section: Discussionmentioning
confidence: 99%